The Use of Cooperative Learning Through Tai (Team Assisted Individualization) In Reading Comprehension - Ermawati Zulikhatin Nuroh; Vidya Mandarani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
Cooperative Learning is a teaching arrangement that refers to small, heterogeneous groups of students working together to achieve a common goal (Kagan, 1994). This research is done to know the response of students used cooperative learning in reading comprehension. The data of this study analyzed qualitatively without applying statistical calculations. The subject of the study were the students of the first semester in Midwifery faculty of Universitas Muhammadiyah Sidoarjo . There researcher used one class which consist 29 students. The students gave the positive responses and dominantly agreed to the implementation of cooperative learning type Team Assisted Individualization (TAI) in reading comprehension. From the questionnaire, the researcher concludes that are 40% students are agreed, 50% students strongly agree, and 10% less agree Â with cooperative learning type Team Assisted Individualization (TAI) in reading comprehension. The conclusion is students respond well to cooperative learning model type Team Assisted Individualization (TAI) to improve students' reading comprehension. This cooperative learning type Team Assisted Individualization (TAI) can be the one of the model to teach reading comprehension.